AN APPROXIMATE FORMULA FOR THE STRESS INTENSITY FACTOR FOR THE PRESSURIZED STAR CRACK - D. L. CLEMENTS; N. WIDANA (Jurnal Matematika, 2007)
An elementary approximate formula for the stress intensity factor for the pressurized starcrack is estab-lished. The formula is sufficiently accurate to be used in practical applications inplace of the more complex formulas derived by Westmann [1] and Williams [2]. © 2003 ElsevierScience Ltd. All rights reserved.